2018
DOI: 10.3390/molecules23102451
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides Derived from Red Seaweed: Production, Properties, and Potential Health and Cosmetic Applications

Abstract: Because of their potential use as functional ingredients in human nutrition, oligosaccharides derived from natural sources are receiving paramount consideration. Red seaweed, a proven rich source of agar and carrageenan, is one of the most abundantly present sources of such oligosaccharides. Agaro-oligosaccharides (AOS) and carrageenan-oligosaccharides (COS) are produced from agar and carrageenan, respectively, through chemical and enzymatic hydrolyses. Enzymatic hydrolysis of agar and carrageenan into oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 104 publications
0
96
2
Order By: Relevance
“…Physical-chemical properties and biological activities of their derivatives are of great interest for study. Previous works showed they have the potential to be used as bioactive molecules and functional materials in food, pharmaceutical, and cosmetic industries [3][4][5]. Among seaweed polysaccharides, agar and carrageenan are valuable sources of various oligosaccharides with beneficial effects for human health, and these effects depend on the degree of depolymerization [6].…”
Section: Introductionmentioning
confidence: 99%
“…Physical-chemical properties and biological activities of their derivatives are of great interest for study. Previous works showed they have the potential to be used as bioactive molecules and functional materials in food, pharmaceutical, and cosmetic industries [3][4][5]. Among seaweed polysaccharides, agar and carrageenan are valuable sources of various oligosaccharides with beneficial effects for human health, and these effects depend on the degree of depolymerization [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the most promising components of dietary fiber, polysaccharides and oligosaccharides derived from marine algae contain unique substitutions, such as sulfation or carboxylation [29], which may possess different activities for human health, unlike those commonly found in fruits and vegetables. As a result, an increasing number of novel marine-derived polysaccharides and oligosaccharides is being discovered and their potential health-promoting properties are being recognized [30][31][32]. NT, the predominant member of the neoagarooligosaccharides that can inhibit bacterial growth and stimulate macrophages [15], is known to possess properties to modulate intestinal microbiome [17].…”
Section: Discussionmentioning
confidence: 99%
“…human health and may have a wide range of applications (9). In a review by Cheong et al (10), the notable biological activity of oligosaccharides from red seaweed was suggested to support their development for use in functional foods and the pharmaceutical industry. Therefore, polysaccharides, oligosaccharides and their derivates are of great interest to researchers.…”
Section: Gamma-irradiation Degraded Sulfated Polysaccharide From a Nementioning
confidence: 99%